Non-neoplastic Proliferative Processes - Fonseca, Felipe Paiva; Miyahara, Glauco Issamu [UNESP]; Junior, Hercílio Martelli; Scarini, João Figueira; Innocentini, Lara Maria Alencar Ramos (Springer Nature, 2023)
Non-neoplastic proliferative processes are lesions frequently found in the oral cavity and are characterized by inflammatory processes causing tissue proliferation. These lesions are found in the general population and can be commonly seen in the day-to-day clinical practice of dentists. In this chapter, we provide an overview of the most common oral non-neoplastic proliferative processes and a concise therapeutic protocol that will give clinicians practical guidance on the management of these lesions.
Keywords: Fibrous hyperplasia; Non-neoplastic proliferative processes; Peripheral ossifying fibroma; Pyogenic granuloma